INNOVATIVE WAYS FOR INCREASING EFFICIENCY OF MELIORATIVE MEASURES IN AGRICULTURE - Sultanov, Bakhodir; Muminov, Nozim; Egamberdiev, Farmonqul; Egamberdieva, Lola (International Journal of Psychosocial Rehabilitation, 2020)
The article developed a methodological approach to determining the causal relationship between land reclamation and land productivity in the Central Asian region, in particular in Uzbekistan, and the amount of damage caused by land reclamation, taking into account the market value of agricultural products. At the same time, in the course of the study, indicators were developed to assess the reclamation state of the land, taking into account the risk values of indicators such as “land use coefficient”, “salinity level”, “groundwater level”, “soil humus content” that affect the state reclamation system. It is also based on the optimal allocation of funds for reclamation measures, which provides a balance of the existing reclamation status of the region and environmental protection based on the efficient use of limited resources.